Internalization Strategy of Religious and Moral Values for Early Childhood - Muzakkir, Ahmad; Muhammad, Soleh (Bestari, 2024)
This study seeks to identify ways for the internalization of religious ideals and morals in early life. This study employs a literature review methodology, which entails the critical analysis of data obtained from various literary materials, including novels, journals, and scientific publications. The study's findings demonstrate that Islamic teachings regard early childhood education as a crucial element in cultivating robust religious ethics and ideals. In this context, eleven successful tactics have been found, including fostering a sense of love for Allah, establishing a sense of security, and promoting environmental observation. These tactics, grounded in the teachings of the Prophet Muhammad and endorsed by Muslim authorities, can be executed by educators and parents. The surrounding environment, including family and classmates, significantly influences the development of children's character. A holistic approach encompasses a concealed curriculum that reinforces religious beliefs and ethics in early life via exemplification, appreciation for diversity, environmental stewardship within schools, and disciplinary practices that align with the moral objectives of education.